2017
DOI: 10.1001/jama.2017.5150
|View full text |Cite
|
Sign up to set email alerts
|

Postmarket Safety Events Among Novel Therapeutics Approved by the US Food and Drug Administration Between 2001 and 2010

Abstract: IMPORTANCE Postmarket safety events of novel pharmaceuticals and biologics occur when new safety risks are identified after initial regulatory approval of these therapeutics. These safety events can change how novel therapeutics are used in clinical practice and inform patient and clinician decision making.OBJECTIVES To characterize the frequency of postmarket safety events among novel therapeutics approved by the US Food and Drug Administration (FDA), and to examine whether any novel therapeutic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
239
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(250 citation statements)
references
References 9 publications
3
239
4
4
Order By: Relevance
“…We supplemented our MedWatch-based dataset by examining every FDA Drug Safety Communication between January 2008 and June 2015 (614 communications), and included additional BBWs not listed on MedWatch. We also included BBWs identified in relevant BBW literature [4,7]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We supplemented our MedWatch-based dataset by examining every FDA Drug Safety Communication between January 2008 and June 2015 (614 communications), and included additional BBWs not listed on MedWatch. We also included BBWs identified in relevant BBW literature [4,7]. …”
Section: Methodsmentioning
confidence: 99%
“…Of novel therapeutics approved between 1996 and 2012, almost three quarters of BBWs were issued at the time of FDA approval, but over 40% of drugs receiving BBWs acquired the warnings in the post-marketing period [3]. Additionally, a recent study found that FDA took significant post-marketing safety actions for approximately one-third of novel therapeutics approved between 2001 and 2010, most commonly issuing a new BBW [4]. Further, the likelihood of drugs approved since the passage of the Prescription Drug User Fee Act (PDUFA) in 1992 receiving post-marketing BBWs or being withdrawn has increased compared to drugs approved before this period [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such evidentiary changes may increase the risk that unsafe drugs will enter the market 7684. And most,7374758586 but not all,84 studies suggest that shorter review times are deleterious.…”
Section: Drug Approval Reformmentioning
confidence: 99%
“…28 In Canada, drugs with a priority review were more likely to acquire a serious safety warning than those with a standard review. 29 On the one hand, authorisation of medicines after limited evaluation may be viewed as putting patients at unnecessary risk.…”
Section: Pathways To Promote Early Access To Medicinesmentioning
confidence: 99%